Melatonin improves bone mineral density at the femoral neck in postmenopausal women with osteopenia: a randomized controlled trial - Amstrup, Anne Kristine; Sikjaer, Tanja; Heickendorff, Lene; Mosekilde, Leif; Rejnmark, Lars (Journal of pineal research, 2015)
Melatonin is known for its regulation of circadian rhythm. Recently, studies have shown that melatonin may have a positive effect on the skeleton. By increasing age, the melatonin levels decrease, which may lead to a further imbalanced bone remodeling. We aimed to investigate whether treatment with melatonin could improve bone mass and integrity in humans. In a double‐blind RCT, we randomized 81 postmenopausal osteopenic women to 1‐yr nightly treatment with melatonin 1 mg (N = 20), 3 mg (N = 20), or placebo (N = 41). At baseline and after 1‐yr treatment, we measured bone mineral density (BMD) by dual X‐ray absorptiometry, quantitative computed tomography (QCT), and high‐resolution peripheral QCT (HR‐pQCT) and determined calciotropic hormones and bone markers. Mean age of the study subjects was 63 (range 56–73) yr. Compared to placebo, femoral neck BMD increased by 1.4% in response to melatonin (P < 0.05) in a dose‐dependent manner (P < 0.01), as BMD increased by 0.5% in the 1 mg/day group (P = 0.55) and by 2.3% (P < 0.01) in the 3 mg/day group. In the melatonin group, trabecular thickness in tibia increased by 2.2% (P = 0.04), and volumetric bone mineral density (vBMD) in the spine, by 3.6% (P = 0.04) in the 3 mg/day. Treatment did not significantly affect BMD at other sites or levels of bone turnover markers; however, 24‐hr urinary calcium was decreased in response to melatonin by 12.2% (P = 0.02). In conclusion, 1‐yr treatment with melatonin increased BMD at femoral neck in a dose‐dependent manner, while high‐dose melatonin increased vBMD in the spine. Further studies are needed to assess the mechanisms of action and whether the positive effect of nighttime melatonin will protect against fractures.